The Effectiveness of Role Play in Improving Students’ Speaking Skills at Private Junior High School in Makassar - Mir'ah Azizah (Universitas Negeri Makassar, 2022)
ABSTRACT This study aims to improve the ability to speak Mandarin in private junior high school students in Makassar. This study used the Mandarin speaking training method using the Role Play by involving 20 respondents or training participants. From the results of this research, it was found that the Mandarin language training method with the mentoring approach, role playing technique training and drama practice entitled